A Place for Every Event and Every Event in Its Place: Memory for Locations and Activities by 4-Year-Old Children. Issue 2 (14th March 2016) - Bauer, Patricia J.; Stewart, Rebekah; White, Elizabeth A.; Larkina, Marina
Abstract : Episodic memories are of specific events and experiences associated with particular times and places. Whereas memory for the temporal aspects of past events has been a focus of research attention, memory for the location in which events were experienced has been less fully investigated. The limited developmental research suggests that preschool-age children, in particular, may have difficulty remembering the location in which they experienced specific events. In 2 experiments, 4-year-old children engaged in 4 unique activities in 4 unique locations in and around a laboratory suite. In Experiment 1, the children had high levels of recall of the activities, the locations, and the conjunctions of activities and locations, implying that they had formed memory representations that featured activities bound in locations. In Experiment 2, we tested whether 1 element of the bound representation—the location of an activity—served as a reliable cue to recall of the other element—the activity itself. The test was positive, providing further evidence that 4-year-old children form mnemonic conjunctions of activities and locations. The results imply that important elements of episodic memory are available to young children.